Development of Social Enterprises as Way of Mitigating the Social Situation in the Donbass - Lyakh, O.V. (Економічний вісник Донбасу, 2014)
The aim of the paper is to investigate the European experience of social enterprises disseminating, i.e. the definition of social enterprises, their legal forms, forms of social enterprises support, as well as to explore how this experience could be applied in Ukraine, especially in the Donbas region. The findings from the research provide a more holistic understanding of growth of social enterprise sector in the OECD countries. This detail adds to an understand the researched topic in the local context, puts forward recommendations on what is required to legitimize social enterprise in Ukraine, and allows to determine what measures are appropriate for fostering social enterprises sector growth in Ukraine and in the region Donbass which is suffering from military conflict. Outcomes facilitates forthcoming research and practical activity connected with social enterprises by overcoming the handicaps caused by the lack of legal recognition commonly acceptable in EU definitions of social enterprise, social entrepreneurship as well as the absence of a national statistics of social enterprises and state policy for development of social enterprises, even in case of the Donbass that is urgently needed this sector growth. Мета статті полягає в дослідженні європейського досвіду поширення соціальних підприємств, тобто визначення соціальних підприємств, їх організаційно-правових форм, підтримки соціальних підприємств, а також визначені, як цей досвід може бути застосований в Україні, особливо в регіоні Донбас. Висновки з дослідження забезпечують більш цілісне розуміння зростання сектору соціального підприємництва в країнах ОЕСР. Це додає до розуміння теми дослідження у місцевому контексті, висуває рекомендації про те, що потрібно, щоб узаконити соціальне підприємство в Україні, і дозволяє визначити, які заходи є необхідними для зміцнення зростання сектору соціальних підприємств в Україні і в Донбасі, який страждає від військового конфлікту. Результати полегшують майбутні дослідження і практичну діяльності, пов'язану з соціальними підприємствами, долаючи перешкоди, викликані відсутністю юридичного визнання загальноприйнятого у ЄС визначення соціального підприємства, соціального підприємництва, а також відсутністю національної статистики соціальних підприємств та державної політики в галузі розвитку соціальних підприємств, навіть у разі Донбасу, який терміново потребує зростання цього сектору. Цель статьи заключается в исследовании европейского опыта распространения социальных предприятий, т.е. определения социальных предприятий, их организационно-правовых форм, поддержки социальных предприятий, а также в установлении, как этот опыт может быть применен в Украине, особенно в регионе Донбассе. Выводы исследования обеспечивают более целостное понимание феномена роста сектора социального предпринимательства в странах ОЭСР. Это способствует интерпретации темы исследования в местном контексте, выбору рекомендации относительно того, правового закрепления социальных предприятий в Украине, и позволяет определить, какие меры необходимы для ускорения роста сектора социальных предприятий в Украине и в Донбассе, который страдает от военного конфликта. Полученные результаты облегчают будущие исследования и практическую деятельности, связанную с социальными предприятиями, преодолевая препятствия, вызванные отсутствием юридического признания общепринятого в ЕС определения социального предприятия, социального предпринимательства, а также отсутствием национальной статистики социальных предприятий и не принятием государственной политики поддержки развития социальных предприятий, даже для Донбасса, который остро нуждается в росте этого сектора.